PMRS Studies of Right Frontal Lobe Metabolism in Attention Deficit Hyperactivity Disorder (ADHD) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Proton magnetic resonance spectroscopy (H-MRS) and quantitative morphometric analysis were used to investigate neurometabolite concentrations in the right prefrontal white matter in relation to attention skill and frontal anatomy of 23 children (17 male) with ADHD and 24 matched controls at the University of New Mexico, Albuquerque.